Resin composition and molded article
By using acrylic copolymers as chemical compatibility agents in heterogeneous biodegradable resins, the problems of compatibility and mechanical properties of the resin composition are solved, and the wide application and biodegradability of the resin composition are achieved.
Patent Information
- Application Number
- CN202380041921.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-25
- Filing Date
- 2023-04-12
- Publication Date
- 2025-01-03
AI Technical Summary
In the prior art, the heterogeneous biodegradable resin compositions deteriorate mechanical properties when using physical compatible agents, and the chemical compatible agents cause rapid increase in viscosity, which is difficult to control, limiting their application expansion.
The use of acrylic copolymers is used as chemical compatibility agents to improve compatibility between PBAT and PLA by adjusting its structure, inhibiting the increase in viscosity, and expanding the use of the resin composition.
Improved compatibility and mechanical properties of the resin composition are achieved, ensuring its processability and biodegradability in a variety of formulations and uses.
Smart Images

Figure CN119256047A_ABST
Abstract
Description
[0001] [CROSS-REFERENCE TO RELATED APPLICATIONS]
[0002] This application claims priority to Korean Patent Application No. 10-2022-0064184 filed on May 25, 2022, the disclosure of which is incorporated into this specification by reference. Technical Field
[0003] The present invention relates to a resin composition and a biodegradable molded product molded therefrom. Background Art
[0004] Thermoplastic resins have excellent mechanical and chemical properties and are therefore used in various fields such as drinking water containers, medical uses, food packaging, food containers, automotive molded products, and agricultural plastics.
[0005] Among them, polyethylene films are mainly used as heat-sealed bags for food packaging, agricultural mulch films, etc. because of their excellent mechanical properties, non-toxicity to the human body, and continuous deformation when heated.
[0006] Heat-seal bags for food packaging are widely used for vacuum packaging of food, etc., and polyethylene films that can achieve excellent adhesive strength even at low sealing temperatures are mainly used for heat-seal bags for food packaging.
[0007] Agricultural mulch is commonly used for covering farming methods. Mulch is a material that covers the surface of the soil when planting crops. When the upper surface of the soil is covered with various materials, weeds can be prevented from growing, pests can be prevented, and the use of pesticides can be reduced. In addition, the temperature of the soil can be easily controlled, beneficial bacteria can be grown in the soil, soil erosion can be prevented, and soil moisture can be maintained. Examples of mulch materials can include straw, leaves of crops such as grass, or polyolefin films, and synthetic resins such as polyethylene films are usually mainly used.
[0008] However, polyethylene films do not decompose in the natural environment and also have limitations in recycling. Specifically, recently, a phenomenon in which plastics such as waste polyethylene films are input into the ocean and broken into very tiny microplastics due to backflow and sunlight in the ocean is a newly emerging problem. It is known that more than billions to tens of billions of such microplastics float in the ocean in uncountable numbers, are input into the bodies of marine organisms, accumulate in the ecosystem, and affect the entire food chain.
[0009] Therefore, recently, the attention to biodegradable plastics has increased. Among biodegradable plastics, polybutylene adipate terephthalate (hereinafter, referred to as PBAT) and polylactic acid (hereinafter, referred to as PLA) have attracted people's attention as biodegradable plastics, and people continue to work hard to improve the compatibility of PBAT and PLA in a biodegradable resin composition containing both PBAT and PLA.
[0010] The compatibilizer for the biodegradable resin composition comprising PBAT and PLA can be divided into physical compatibilizer and chemical compatibilizer according to the working principle. As physical compatibilizer, representative is to use the compatibilizer of the copolymer comprising PBAT or PLA. However, when using such physical compatibilizer, because physical compatibilizer plays the effect similar to plasticizer, there is the shortcoming of mechanical property degradation.
[0011] Meanwhile, patent registration number 10-2045863 (patent document 1) discloses a biodegradable polyester film, which includes an epoxy group and includes a copolymer in which styrene, acrylate and / or methacrylate are used as a substrate. When the copolymer disclosed in patent document 1 is used as a compatibilizer for PBAT and PLA, the use of more than a certain amount of the copolymer results in not only forming PBAT-g-PLA at the interface between PBAT and PLA, but also forming a large amount of PBAT-g-PBAT and / or PLA-g-PLA shortcomings in each resin, thereby causing the viscosity of the resin composition to increase rapidly. Due to the rapid increase in viscosity that is difficult to control during the processing of the resin composition, the expansion of the application of the resin composition is limited. Therefore, in the biodegradable resin composition comprising a heterogeneous biodegradable resin, while maintaining the performance as a chemical compatibilizer, it is important to ensure that the compatibilizer that can ensure processability by controlling the viscosity increase within an appropriate range is important.
[0012] Prior art literature
[0013] [Patent Document]
[0014] (Patent Document 1) KR 10-2045863B1 Summary of the invention
[0015] Technical issues
[0016] The present invention is made to solve the problems of the prior art and provides a biodegradable resin composition comprising a heterogeneous biodegradable resin, wherein the compatibility is improved by using a chemical compatibilizer for improving the compatibility between the heterogeneous biodegradable resins, thereby improving the mechanical properties.
[0017] That is, an object of the present invention is to provide a biodegradable resin composition comprising a heterogeneous biodegradable resin, wherein the resin composition has improved compatibility due to a chemical compatibilizer and thus has improved mechanical properties.
[0018] In addition, another object of the present invention is to provide a resin composition, wherein even if the same amount of a compatibilizer as the copolymer disclosed in Patent Document 1 is used, a rapid increase in viscosity can be suppressed and compatibility can be improved by adjusting the structure of an acrylic copolymer as a compatibilizer for a heterogeneous biodegradable resin, thereby expanding the use of the resin composition to various formulations and uses.
[0019] Furthermore, another object of the present invention is to provide a molded article which is molded from the resin composition and exhibits biodegradability.
[0020] Technical Solution
[0021] In order to solve the above limitations, the present invention provides a resin composition and a molded article.
[0022] (1) The present invention provides a resin composition comprising: a first biodegradable resin and a second biodegradable resin; and at least one of an acrylic copolymer and a compatible portion formed by the acrylic copolymer, wherein the acrylic copolymer comprises a methyl (meth)acrylate monomer unit, a (meth)acrylate monomer unit containing an epoxy group, and an alkyl (meth)acrylate monomer unit having 2 to 10 carbon atoms, and the content of the (meth)acrylate monomer unit containing an epoxy group is 15 wt % to 60 wt %.
[0023] (2) In the above (1) of the present invention, there is provided the resin composition, wherein the first biodegradable resin comprises an aliphatic polyester unit and an aromatic polyester unit.
[0024] (3) In the above (1) or (2) of the present invention, there is provided the resin composition, wherein the first biodegradable resin comprises polybutylene adipate terephthalate.
[0025] (4) In any one of the above (1) to (3) of the present invention, there is provided the resin composition, wherein the second biodegradable resin comprises polylactic acid.
[0026] (5) In any one of the above (1) to (4) of the present invention, there is provided the resin composition, wherein the content of the second biodegradable resin is 1 part by weight to 50 parts by weight based on 100 parts by weight of the first biodegradable resin.
[0027] (6) In any one of the above (1) to (5) of the present invention, there is provided the resin composition, wherein the content of at least one of the acrylic copolymer and the compatible part formed by the acrylic copolymer is 0.01 parts by weight to 10 parts by weight based on 100 parts by weight of the first biodegradable resin.
[0028] (7) In any one of the above (1) to (6) of the present invention, the resin composition is provided, wherein the acrylic copolymer contains 25% to 65% by weight of methyl (meth)acrylate monomer units, 15% to 60% by weight of (meth)acrylate monomer units containing epoxy groups and 5% to 30% by weight of (meth)acrylate alkyl ester monomer units having 2 to 10 carbon atoms.
[0029] (8) In any one of the above (1) to (7) of the present invention, there is provided the resin composition, wherein the epoxy equivalent weight (EEW) of the acrylic copolymer is 200 g / eq to 800 g / eq.
[0030] (9) In any one of the above (1) to (8) of the present invention, there is provided the resin composition, wherein the weight average molecular weight of the acrylic copolymer is 10,000 to 100,000.
[0031] (10) In any one of the above (1) to (9) of the present invention, there is provided the resin composition, wherein the acrylic copolymer has a glass transition temperature of 45°C to 85°C.
[0032] (11) In any one of the above (1) to (10) of the present invention, there is provided the resin composition, wherein the weight average molecular weight of the entire resin composition is 100,000 to 200,000.
[0033] (12) In any one of the above (1) to (11) of the present invention, there is provided the resin composition, wherein the melt flow index of the resin composition measured at 190°C with a load of 5 kg according to ASTM D1238 is 3 g / 10 min to 13.5 g / 10 min.
[0034] (13) In any one of the above (1) to (12) of the present invention, there is provided the resin composition, wherein the tensile strength of the resin composition measured according to ASTM D638 is 245 kgf / cm 2 Up to 500kgf / cm 2 .
[0035] (14) In any one of the above (1) to (13) of the present invention, there is provided the resin composition, wherein the elongation of the resin composition measured according to ASTM D638 is 400% or more.
[0036] (15) In any one of the above (1) to (14) of the present invention, there is provided the resin composition, wherein, when a sample of the resin composition is magnified at a magnification of 25,000 using a transmission electron microscope, the average diameter of the domain is 1 μm or less relative to the major diameter of the observed domain.
[0037] (16) The present invention provides a molded product molded from the resin composition described in any one of (1) to (15).
[0038] Beneficial Effects
[0039] The resin composition of the present invention is a biodegradable resin composition comprising a heterogeneous biodegradable resin, the resin composition having improved compatibility due to a chemical compatibilizer, and thus having improved mechanical properties.
[0040] Furthermore, in the resin composition of the present invention, even if the same amount of compatibilizer as that of the copolymer disclosed in Patent Document 1 is used, a rapid increase in viscosity can be suppressed and compatibility can be improved by adjusting the structure of the acrylic copolymer as a compatibilizer for a heterogeneous biodegradable resin, thereby expanding the use of the resin composition to various formulations and uses.
[0041] Furthermore, the molded article molded from the resin composition of the present invention has improved mechanical properties and exhibits biodegradability. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is an image obtained by capturing an image of the surface of a sample of the resin composition prepared according to Example 3 of the present invention and magnifying it at a magnification of 25,000 using a transmission electron microscope.
[0043] Figure 2 is an image obtained by capturing an image of the surface of a sample of the resin composition prepared in Comparative Example 1 of the present invention and magnifying it at a magnification of 25,000 using a transmission electron microscope. DETAILED DESCRIPTION
[0044] Hereinafter, the present invention will be described in more detail to help understanding of the present invention.
[0045] It should be understood that the words or terms used in the specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it should be further understood that, based on the principle that the inventor can appropriately define the meanings of words or terms to best explain the present invention, the words or terms should be interpreted as having a meaning consistent with their meanings in the context of the relevant technology and the technical concept of the present invention.
[0046] As used herein, the term "monomer unit" may refer to a component, structure, or material itself derived from a monomer, and for a specific example, may refer to a repeating unit formed in a polymer by inputting a monomer to participate in a polymerization reaction.
[0047] As used herein, the term "composition" includes not only reaction products and decomposition products formed from the materials of the corresponding composition, but also includes mixtures comprising the materials of the corresponding composition.
[0048] The invention provides a resin composition.
[0049] The resin composition may be a biodegradable resin composition comprising a heterogeneous biodegradable resin. For a specific example, the resin composition may include a first biodegradable resin and a second biodegradable resin and at least one of an acrylic copolymer and a compatible portion formed by the acrylic copolymer, wherein the acrylic copolymer may include a (meth) methyl acrylate monomer unit, a (meth) acrylic acid ester monomer unit containing an epoxy group, and a (meth) acrylic acid alkyl ester monomer unit having 2 to 10 carbon atoms, and the content of the (meth) acrylic acid ester monomer unit containing an epoxy group is 15 wt % to 60 wt %.
[0050] The types of the first biodegradable resin and the second biodegradable resin can be different from each other, and any known biodegradable resin can be used. For a specific example, the first biodegradable resin can be a polyester resin comprising an aliphatic polyester unit and an aromatic polyester unit. For a more specific example, the first biodegradable resin can include polybutylene adipate terephthalate (PBAT). PBAT is a random copolymer of adipic acid, 1,4-butanediol and terephthalic acid, and is considered to be an alternative biodegradable resin for low-density polyethylene. Specifically, PBAT can ensure the mechanical properties of the aromatic polyester unit formed by terephthalic acid and 1,4-butanediol, while ensuring the biodegradability of the aliphatic polyester unit formed by adipic acid and 1,4-butanediol.
[0051] Any biodegradable resin different from the first biodegradable resin can be used as the second biodegradable resin, and for a specific example, the second biodegradable resin can include polylactic acid (PLA). PLA corresponds to an eco-friendly biodegradable resin made of biomaterials and naturally decomposed into water and carbon dioxide by the action of microorganisms within a few months.
[0052] The resin composition may include 1 to 50 parts by weight of the second biodegradable resin relative to 100 parts by weight of the first biodegradable resin. For a specific example, the resin composition may include more than 1 part by weight, more than 5 parts by weight, more than 10 parts by weight, more than 15 parts by weight, more than 20 parts by weight, or more than 25 parts by weight, and less than 50 parts by weight, less than 49 parts by weight, less than 48 parts by weight, less than 47 parts by weight, less than 46 parts by weight, less than 45 parts by weight, less than 44 parts by weight, or less than 43 parts by weight of the second biodegradable resin relative to 100 parts by weight of the first biodegradable resin, and within this range, mechanical properties and processability may be more excellent.
[0053] The resin composition may include 0.01 to 10 parts by weight of an acrylic copolymer and at least one of the compatible parts formed by the acrylic copolymer, relative to 100 parts by weight of the first biodegradable resin. For a specific example, the resin composition may include 0.01 parts by weight or more, 0.05 parts by weight or more, 0.10 parts by weight or more, 0.11 parts by weight or more, 0.12 parts by weight or more, and 10 parts by weight or less, 9 parts by weight or less, 8 parts by weight or less, 7 parts by weight or less, 6 parts by weight or less, 5 parts by weight or less, 4 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, 0.5 parts by weight or less, 0.4 parts by weight or less, 0.3 parts by weight or less, or 0.2 parts by weight or less of the acrylic copolymer and at least one of the compatible parts formed by the acrylic copolymer, relative to 100 parts by weight of the first biodegradable resin.
[0054] The acrylic copolymer may be a copolymer containing a reactive functional group such as an epoxy group, and may be contained in the resin composition as a chemical compatibilizer for improving the compatibility of the heterogeneous biodegradable resin. The acrylic copolymer may be present in the resin composition as it is, or may be present in the form of a compatible portion through chemical bonding through the reaction of the reactive functional group with the heterogeneous biodegradable resin, or the above two forms may coexist.
[0055] The acrylic copolymer may be an acrylic copolymer copolymerized by including a methyl (meth)acrylate monomer, a (meth)acrylate monomer containing an epoxy group, and an alkyl (meth)acrylate monomer having 2 to 10 carbon atoms. For a specific example, the acrylic copolymer may be a random copolymer or a linear random copolymer copolymerized by including a methyl (meth)acrylate monomer, a (meth)acrylate monomer containing an epoxy group, and an alkyl (meth)acrylate monomer having 2 to 10 carbon atoms. Herein, "(meth)acrylate" refers to both acrylate and methacrylate.
[0056] The acrylic copolymer may include a (meth) methyl acrylate monomer unit formed by a (meth) methyl acrylate monomer in an amount of 25 to 65 weight %. For a specific example, the acrylic copolymer may include a (meth) methyl acrylate monomer unit formed by a (meth) methyl acrylate monomer in an amount of more than 25 weight %, more than 30 weight %, more than 35 weight % or more than 40 weight %, and less than 65 weight %, less than 60 weight %, less than 55 weight % or less than 50 weight %. Within this range, the acrylic copolymer may have excellent miscibility with PLA and relatively good affinity with PBAT, and therefore the compatibility of PBAT with PLA may be further improved.
[0057] Acrylic copolymer can include the (meth) acrylate monomer unit containing epoxy group formed by the (meth) acrylate monomer containing epoxy group, and its amount is 15 weight % to 60 weight %.For specific example, acrylic copolymer can include the (meth) acrylate monomer unit containing epoxy group formed by the (meth) acrylate monomer containing epoxy group, and its amount is more than 15 weight %, more than 20 weight %, more than 25 weight %, more than 30 weight %, more than 35 weight % or more than 40 weight %, and less than 60 weight %, less than 55 weight %, less than 50 weight % or less than 45 weight %.Within the scope, the flexibility of polymer chain can be increased, and the compatibility between heterogeneous biodegradable resins can be further improved, and specifically, when film is prepared by resin combination, chain diffusion and entanglement at interface between film can be increased.
[0058] The (meth) acrylate monomer containing an epoxy group may be a (meth) acrylate monomer containing a glycidyl group, and for a specific example, may be a glycidyl (meth) acrylate monomer. In the (meth) acrylate monomer containing an epoxy group, the epoxy group contained in the monomer may react with the hydroxyl group (-OH) or carboxylic acid group (-COOH) contained in PBAT or PLA, thereby imparting the function of a chemical compatibilizer. In addition, when the reaction occurs at the interface between PBAT and PLA, the compatibility and interfacial adhesion between PBAT and PLA may be further improved.
[0059] The acrylic copolymer can include the (meth) alkyl acrylate monomer units with 2 to 10 carbon atoms formed by the (meth) alkyl acrylate monomers with 2 to 10 carbon atoms, and its amount is 5 weight % to 30 weight %.For specific example, the acrylic copolymer can include the (meth) alkyl acrylate monomer units with 2 to 10 carbon atoms formed by the (meth) alkyl acrylate monomers with 2 to 10 carbon atoms, and its amount is more than 5 weight %, more than 10 weight % or more than 15 weight %, and less than 30 weight %, less than 25 weight % or less than 20 weight %.Within this range, the flexibility of polymer chain can be increased, and the compatibility between heterogeneous biodegradable resins can be further improved, particularly, when film is prepared by resin combination, chain diffusion and entanglement at interface between film can be increased.
[0060] The (meth)acrylic acid alkyl ester monomer having 2 to 10 carbon atoms may be at least one selected from ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, dodecyl (meth)acrylate, isobornyl (meth)acrylate, and lauryl (meth)acrylate. For a specific example, the (meth)acrylic acid alkyl ester monomer having 2 to 10 carbon atoms may be an (meth)acrylic acid alkyl ester monomer having 3 to 9 or 4 to 8 carbon atoms, and for a more specific example, may be at least one selected from butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate.
[0061] The acrylic copolymer can be prepared by emulsion polymerization of a polymerization composition comprising a polymerization initiator, an emulsifier, and a monomer mixture comprising a methyl (meth)acrylate monomer, a (meth)acrylate monomer containing an epoxy group, and an alkyl (meth)acrylate monomer having 2 to 10 carbon atoms.
[0062] During the polymerization of the acrylic copolymer, the polymerization can be carried out at different polymerization temperatures for different polymerization times as required. For a specific example, the polymerization can be carried out at a polymerization temperature ranging from 50° C. to 200° C. for 0.5 hour to 20 hours.
[0063] The polymerization initiator may be an inorganic or organic peroxide, and as specific examples, may be a water-soluble polymerization initiator including potassium persulfate, sodium persulfate, ammonium persulfate, and the like, and an oil-soluble polymerization initiator including cumene hydroperoxide, benzoyl peroxide, and the like.
[0064] An activator may be used together with the polymerization initiator to promote the triggering of the peroxide reaction, and at least one selected from sodium formaldehyde sulfoxylate, sodium ethylenediaminetetraacetate, ferrous sulfate and glucose may be used as the activator.
[0065] The polymerization initiator may be added in an amount of 0.1 to 10 parts by weight, and for a specific example, 0.1 to 5 parts by weight, relative to 100 parts by weight of the monomer mixture on a dry basis.
[0066] Polymerization can be carried out by further including a chain transfer agent for improving polymerization efficiency. Chain transfer agent can be used for introducing homopolymer into micelle during polymerization, and the homopolymer is a polymer consisting of only one type of monomer. Chain transfer agent can be a straight or branched alkyl mercaptan compound with 5 to 20 carbon atoms, and for specific examples, can be hexanethiol, cyclohexanethiol, adamantanethiol, heptylthiol, octylthiol, nonylthiol, decyl mercaptan, undecyl mercaptan, dodecanethiol, hexadecyl mercaptan, octadecyl mercaptan, etc. In addition, relative to the monomer mixture of 100 weight parts, by dry weight, the addition of chain transfer agent can be 0.1 weight part to 10 weight parts, and for specific examples, can be 0.1 weight part to 5 weight parts.
[0067] The emulsion polymerization may be performed by including steps (S10) to (S30).
[0068] (S10) Step: preparing an emulsion by dispersing an emulsifier in a solvent.
[0069] (S20) Step: Preparing a pre-emulsion by mixing a monomer mixture including a monomer component with an emulsifier and the like.
[0070] (S30) step: mixing the emulsion prepared in step (S10) with the pre-emulsion prepared in step (S20), and performing emulsion polymerization in the presence of a polymerization initiator.
[0071] The emulsion polymerization for polymerizing the acrylic copolymer may be performed according to steps (S10) to (S30).
[0072] First, in step (S10), an emulsion containing an emulsifier is prepared. This step is a step separated from the following pre-emulsion preparation process. As an emulsifier, an anionic emulsifier can be used alone, or anionic emulsifiers, cationic emulsifiers and nonionic emulsifiers can be used together, and the emulsifier component can be mixed with a solvent such as water to prepare the emulsion. In the preparation process of the emulsion, initial micelle particles with a size of several nanometers can be stably formed. Step (S20) is a preparation step of a pre-emulsion containing a monomer mixture, wherein the pre-emulsion is prepared by mixing the above-mentioned monomers, emulsifiers, etc. with water. In this case, as an emulsifier, an anionic emulsifier can be used alone, or anionic emulsifiers can be used together with nonionic emulsifiers. In this process, nano-sized latex particles can be formed in the pre-emulsion. That is, the above-mentioned emulsifier can be used in the emulsion preparation step and / or the pre-emulsion preparation step. In step (S30), after the polymerization initiator is added to the emulsion thus prepared, the pre-emulsion and the polymerization initiator are continuously added in equal proportions over a predetermined period of time.
[0073] Relative to 100 parts by weight of the monomer mixture, the amount of the polymerization initiator added to the emulsion can be greater than 0 parts by weight and equal to or less than 1 part by weight, and the amount of the polymerization initiator added together with the pre-emulsion can be 0.1 parts by weight to 2 parts by weight relative to 100 parts by weight of the monomer mixture, and the continuous input time can be about 3 hours to about 7 hours. Through this process, the monomer or polymer suspended in the pre-emulsion can be put into the initial particles formed in the emulsion. Then, the product of the reaction can undergo a thermal polymerization process in the presence of another polymerization initiator, and through this process, the residual monomer is polymerized. In this case, relative to 100 parts by weight of the monomer mixture, 0.1 parts by weight to 10 parts by weight of the polymerization initiator can be further added, and thermal polymerization can be performed at a temperature of about 75°C to about 85°C for about 40 minutes to about 80 minutes. This emulsion polymerization method is divided into an emulsion preparation process and a pre-emulsion preparation process, and can be carried out later by a simple method of mixing the pre-emulsion with the emulsion, thereby improving process stability and productivity compared with conventional methods.
[0074] The emulsifier used in emulsion polymerization can include at least one selected from anionic emulsifiers, cationic emulsifiers and nonionic emulsifiers. The emulsifier is a material with both hydrophilic groups and hydrophobic groups, forms a micellar structure during emulsion polymerization, and enables the polymerization of each monomer to occur in the micellar structure. Commonly used emulsifiers in emulsion polymerization can be divided into anionic emulsifiers, cationic emulsifiers and nonionic emulsifiers, and with regard to the polymerization stability in emulsion polymerization, two or more emulsifiers can be mixed and used. For specific examples, nonionic emulsifiers can include at least one selected from polyoxyethylene alkyl aryl ether, polyoxyethylene alkylamine and polyoxyethylene alkyl ester. In addition, anionic emulsifiers can include at least one selected from alkyl diphenyl ether sodium disulfonate, polyoxyethylene alkyl ether sodium sulfate, polyoxyethylene aryl ether sodium sulfate, alkyl sodium sulfate, alkyl benzene sodium sulfonate and dialkyl sodium sulfosuccinate. These can be used alone, or as a mixture of two or more, and may be more effective when used with a mixture of anionic emulsifiers and nonionic emulsifiers. In addition, the emulsifier may be used in an amount of about 0.1 parts by weight to about 10 parts by weight, or about 1 part by weight to about 5 parts by weight, relative to 100 parts by weight of the total monomer components used to prepare the latex particles.
[0075] In addition to the emulsifier or monomer components, the composition for polymerization may further include an aqueous solvent such as water. In this case, in terms of stability of latex particles and viscosity control, the amount of the aqueous solvent may be about 10 parts by weight to 1,000 parts by weight relative to 100 parts by weight of the latex particles, and the aqueous solvent may be used so that the total solid content (TSC) is adjusted to about 10% by weight to about 60% by weight relative to the total amount of the composition.
[0076] The acrylic copolymer may have an epoxy equivalent weight (EEW) of 200 g / eq to 800 g / eq. For specific examples, the epoxy equivalent weight (EEW) of the acrylic copolymer may be 200 g / eq or more, 210 g / eq or more, 220 g / eq or more, 230 g / eq or more, 240 g / eq or more, 250 g / eq or more, 260 g / eq or more, 270 g / eq or more, 280 g / eq or more, 290 g / eq or more, 300 g / eq or more, 310 g / eq or more, 320 g / eq or more, 330 g / eq or more, 340 g / eq or more, or 350 g / eq or more. The compatibility of the biodegradable resins in the heterogeneous phase can be further improved. Specifically, when the biodegradable resin is a polyester resin, the reaction with the hydroxyl group or the carboxylic acid group of the polyester resin is effectively carried out, so the performance as a chemical compatibilizer can be further improved.
[0077] The acrylic copolymer may have a weight average molecular weight of 10,000 to 100,000. For specific examples, the weight average molecular weight of the acrylic copolymer may be more than 10,000, more than 15,000, more than 20,000, more than 25,000, or more than 30,000, and the weight average molecular weight may be less than 100,000, less than 90,000, less than 80,000, less than 70,000, less than 60,000, less than 50,000, or less than 40,000. Within this range, the effect as a chemical compatibilizer may be more excellent without damaging the inherent properties of heterogeneous biodegradable resins, particularly polyester resins. The weight average molecular weight may not be expressed in units, but may be expressed in units of g / mol according to molar mass.
[0078] The glass transition temperature of the acrylic copolymer may be 45° C. to 85° C. For specific examples, the glass transition temperature of the acrylic copolymer may be 45° C. or more, 46° C. or more, 47° C. or more, 48° C. or more, 49° C. or more, 50° C. or more, 51° C. or more, 52° C. or more, 53° C. or more, 54° C. or more, 55° C. or more, 56° C. or more, 57° C. or more, 58° C. or more, or 59° C. or more, and may be 85° C. or less, 84° C. or less, 83° C. or less, 82° C. or less, 81° C. or less, 80° C. or less, 79° C. or less, 78° C. or less, 77° C. or less, 76° C. or less, 75° C. or less, 74° C. or less, 73° C. or less, 72° C. or less, 71° C. or less, or 70° C. or less. Within this range, the resin composition including the heterogeneous biodegradable resin may be more easily processed due to the compatibilizer.
[0079] In the resin composition, the weight average molecular weight of the whole resin composition can be 100,000 to 200,000. For specific examples, the weight average molecular weight of the whole resin composition can be more than 100,000, more than 105,000, more than 110,000, more than 115,000, more than 120,000, more than 125,000 or more than 130,000, and can be less than 200,000, less than 195,000, less than 190,000, less than 185,000, less than 180,000, less than 175,000, less than 170,000, less than 165,000, less than 160,000 or less than 155,000. Within this range, the tensile properties of the resin composition can be further improved.
[0080] As measured according to ASTM D1238 at 190°C with a load of 5kg, the resin composition may have a melt flow index of 3g / 10min to 13.5g / 10min. For specific examples, as measured according to ASTM D1238 at 190°C with a load of 5kg, the melt flow index of the resin composition may be 3g / 10min or more, 4g / 10min or more, 5g / 10min or more, 6g / 10min or more, or 6.5g / 10min or more, and may be 13.5g / 10min or less, 13g / 10min or less, 12.5g / 10min or less, 12g / 10min or less, 11.5g / 10min or less, 11g / 10min or less, 10.5g / 10min or less, 10g / 10min or less, 9.5g / 10min or less, or 9g / 10min or less. Within this range, since the resin composition is excellent in tensile strength and the viscosity is maintained at an appropriate level, workability can be further improved.
[0081] The resin composition may have a thermal conductivity of 245 kgf / cm2 as measured according to ASTM D638. 2 Up to 500kgf / cm 2 For a specific example, the tensile strength of the resin composition measured according to ASTM D638 may be 245 kgf / cm 2 Above, 250kgf / cm 2 Above, 260kgf / cm 2 Above, 270kgf / cm 2 Above, 280kgf / cm 2 Above or 290kgf / cm 2 Above, and can be 500kgf / cm 2 Below, 490kgf / cm 2 Below, 480kgf / cm 2 Below, 470kgf / cm 2 Below, 460kgf / cm 2 Below, 450kgf / cm 2 Below, 440kgf / cm 2 Below, 430kgf / cm 2 Below, 420kgf / cm 2 Below, 410kgf / cm 2 Below, 400kgf / cm 2 Below, 390kgf / cm 2 Below or 380kgf / cm 2 the following.
[0082] The elongation of the resin composition measured according to ASTM D638 can be 400% or more. For specific examples, the elongation of the resin composition measured according to ASTM D638 can be 400% or more, 410% or more, 420% or more, 430% or more, 440% or more, 450% or more, 460% or more, 470% or more, 480% or more, 490% or more, 500% or more, 510% or more, 520% or more, 530% or more, 540% or more, 550% or more, 560% or more, 570% or more, 580% or more, 590% or more, or 600% or more, and can be 700% or less, 690% or less, 680% or less, 670% or less, 660% or less, or 650% or less.
[0083] In the resin composition, when a sample of the resin composition is magnified at a magnification of 25,000 using a transmission electron microscope, the average diameter of the domain relative to the long diameter of the observed domain can be 1 μm or less. For a specific example, in the resin composition, when a sample of the resin composition is magnified at a magnification of 25,000 using a transmission electron microscope, the average diameter of the domain relative to the long diameter of the observed domain can be 1 μm or less, 0.9 μm or less, 0.8 μm or less, 0.7 μm or less, 0.6 μm or less, or 0.5 μm or more, 0.01 μm or more, 0.05 μm or more, 0.1 μm or more, 0.2 μm or more.
[0084] The present invention provides a shaped product.
[0085] The molded product may be a biodegradable molded product molded from the resin composition, ie, a biodegradable resin composition. Here, the molded product includes a film-molded product formed by film forming, an injection-molded product formed by injection molding, and the like.
[0086] The shaped article may be a biodegradable film, and for a specific example, may be an agricultural mulch film or a film used as a food packaging material.
[0087] Hereinafter, embodiments of the present invention will be described in detail so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein.
[0088] Preparation Example and Comparative Preparation Example: Preparation of Acrylic Copolymer
[0089] Preparation Example 1
[0090] Relative to 100 parts by weight of the total weight of methyl methacrylate, glycidyl methacrylate, butyl acrylate and 2-ethylhexyl acrylate as monomers, 200 parts by weight of distilled water and 0.5 parts by weight of sodium dioctyl sulfosuccinate (sodium bis(2-ethylhexyl)sulfosuccinate) as an emulsifier were added to a 3L glass reactor equipped with a thermometer, a stirrer, a dropping funnel, a nitrogen inlet tube and a reflux cooler, and stirred. During the stirring, the inside of the reactor was replaced with nitrogen, and then the glass reactor was heated to 70° C., 0.2 parts by weight of potassium persulfate was added, and the resulting mixture was kept for 30 minutes.
[0091] In addition, 45 parts by weight of methyl methacrylate, 40 parts by weight of glycidyl methacrylate, and 15 parts by weight of butyl acrylate as monomers were put into a beaker and mixed thoroughly for 30 minutes. To the mixture, 0.5 parts by weight of 1-octanethiol as a chain transfer agent was added relative to 100 parts by weight of all monomers, and mixed thoroughly with a stirrer, and then the obtained mixture was continuously added to the glass reactor in equal proportions over 4 hours.
[0092] Then, after 4 hours of polymerization reaction time, the internal temperature of the glass reactor was maintained at 70° C. for 30 minutes and then cooled to room temperature. The obtained emulsion polymerization product was coagulated using an aqueous calcium acetate solution, heat-treated at 85° C., dehydrated, and dried at 60° C. for 16 hours to obtain an acrylic copolymer.
[0093] Preparation Example 2
[0094] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that 15 parts by weight of 2-ethylhexyl acrylate was added instead of 15 parts by weight of butyl acrylate in Preparation Example 1.
[0095] Preparation Example 3
[0096] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that 55 parts by weight were added instead of 45 parts by weight of methyl methacrylate and 30 parts by weight were added instead of 40 parts by weight of glycidyl methacrylate.
[0097] Preparation Example 4
[0098] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that 30 parts by weight were added instead of 45 parts by weight of methyl methacrylate and 55 parts by weight were added instead of 40 parts by weight of glycidyl methacrylate.
[0099] Preparation Example 5
[0100] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that 30 parts by weight of methyl methacrylate was added instead of 45 parts by weight, 55 parts by weight of glycidyl methacrylate was added instead of 40 parts by weight, and 15 parts by weight of 2-ethylhexyl acrylate was added instead of 15 parts by weight of butyl acrylate.
[0101] Preparation Example 6
[0102] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that 55 parts by weight of methyl methacrylate was added instead of 45 parts by weight, 20 parts by weight of glycidyl methacrylate was added instead of 40 parts by weight, and 25 parts by weight of 2-ethylhexyl acrylate was added instead of 15 parts by weight of butyl acrylate.
[0103] Comparative Preparation Example 1
[0104] A commercially available copolymer (a copolymer of methyl methacrylate, butyl acrylate, glycidyl methacrylate, and styrene) used in the preparation of the master batch A described in Patent Document 1 was used.
[0105] Comparative Preparation Example 2
[0106] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that 64 parts by weight were added instead of 45 parts by weight of methyl methacrylate, 2.1 parts by weight were added instead of 40 parts by weight of glycidyl methacrylate, and 33.9 parts by weight were added instead of 15 parts by weight of butyl acrylate.
[0107] Comparative Preparation Example 3
[0108] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that 62.3 parts by weight were added instead of 45 parts by weight of methyl methacrylate, 5.2 parts by weight were added instead of 40 parts by weight of glycidyl methacrylate, and 32.5 parts by weight of 2-ethylhexyl acrylate was added instead of 15 parts by weight of butyl acrylate.
[0109] Comparative Preparation Example 4
[0110] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that 60 parts by weight were added instead of 45 parts by weight of methyl methacrylate, 10 parts by weight were added instead of 40 parts by weight of glycidyl methacrylate, and 30 parts by weight were added instead of 15 parts by weight of butyl acrylate.
[0111] Comparative Preparation Example 5
[0112] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that 10 parts by weight were added instead of 45 parts by weight of methyl methacrylate, 64.8 parts by weight were added instead of 40 parts by weight of glycidyl methacrylate, and 25.2 parts by weight were added instead of 15 parts by weight of butyl acrylate.
[0113] Comparative Preparation Example 6
[0114] An acrylic copolymer was obtained in the same manner as in Preparation Example 1, except that 10 parts by weight were added instead of 45 parts by weight of methyl methacrylate, 75 parts by weight were added instead of 40 parts by weight of glycidyl methacrylate, and 15 parts by weight of 2-ethylhexyl acrylate were added instead of 15 parts by weight of butyl acrylate.
[0115] Comparative Preparation Example 7
[0116] <Preparation of Acrylic Core Latex>
[0117] Relative to 100 parts by weight of the monomers methyl methacrylate, glycidyl methacrylate and butyl acrylate put in the preparation of core and shell, 80 parts by weight of distilled water, 0.2 parts by weight of sodium bicarbonate (NaHCO 3 ), 0.001 parts by weight of ferrous sulfate and 0.18 parts by weight of disodium ethylenediaminetetraacetate were put into a glass reactor with a volume of 3L equipped with a thermometer, a stirrer, a dropping funnel, a nitrogen inlet pipe and a reflux cooler, and stirred. During stirring, the interior of the reactor was replaced with nitrogen, and the internal temperature of the glass reactor was then raised to 50° C. and maintained.
[0118] Separately, in order to prepare a monomer pre-emulsion, 50 parts by weight of distilled water, 0.6 parts by weight of sodium dodecyl sulfate, and 85 parts by weight of butyl acrylate were charged to prepare a monomer pre-emulsion.
[0119] While maintaining the internal temperature of the reactor at 50° C., the prepared monomer pre-emulsion was continuously added for 5 hours, and 0.2 parts by weight of tert-butyl hydroperoxide and 0.2 parts by weight of sodium formaldehyde sulfoxylate as initiators were added to initiate the reaction. 30 minutes after the addition of the monomer pre-emulsion was completed, 0.01 parts by weight of tert-butyl hydroperoxide and 0.02 parts by weight of sodium formaldehyde sulfoxylate were further added, and aged for 1 hour to prepare an acrylic core latex containing an acrylic core polymer. At this time, the polymerization conversion rate was 99%, and the total content of the solid powder was 40% by weight.
[0120] <Preparation of Graft Copolymer Latex>
[0121] While the temperature of the reactor was maintained at 70° C., 10 parts by weight of distilled water and 0.1 parts by weight of sodium lauryl sulfonate were added to the reactor with respect to a total of 100 parts by weight of the monomers methyl methacrylate, glycidyl methacrylate, and butyl acrylate added in the preparation of the core and the shell, and stirred. During the stirring process, the interior of the reactor was replaced with nitrogen.
[0122] Separately, 13 parts by weight of methyl methacrylate, 2 parts by weight of glycidyl methacrylate, and 0.2 parts by weight of 1-octanediol as a chain transfer agent were put into a beaker and sufficiently stirred with a stirrer to prepare a graft monomer mixture.
[0123] The prepared graft monomer mixture was continuously added to the reactor for 1 hour, and graft polymerization was performed to prepare a graft copolymer latex containing a core-shell graft copolymer. At this time, the polymerization conversion rate was 99% and the total content of the solid powder was 42% by weight.
[0124] Comparative Preparation Example 8
[0125] An acrylic core latex was obtained in the same manner as in Comparative Preparation Example 7, except that 80 parts by weight of 2-ethylhexyl acrylate was added instead of 85 parts by weight of butyl acrylate, and a core-shell graft copolymer was obtained in the same manner as in Comparative Preparation Example 7, except that 18 parts by weight of methyl methacrylate was added instead of 13 parts by weight in Comparative Preparation Example 7.
[0126] Comparative Preparation Example 9
[0127] An acrylic core latex was obtained in the same manner as in Comparative Preparation Example 7, except that 80 parts by weight of butyl acrylate was added instead of 85 parts by weight, and a core-shell graft copolymer was obtained in the same manner as in Comparative Preparation Example 7, except that 15 parts by weight of methyl methacrylate was added instead of 13 parts by weight and 5 parts by weight of glycidyl methacrylate was added instead of 2 parts by weight in Comparative Preparation Example 7.
[0128] Comparative Preparation Example 10
[0129] An acrylic core latex was obtained in the same manner as in Comparative Preparation Example 7, except that 80 parts by weight of 2-ethylhexyl acrylate was added instead of 85 parts by weight of butyl acrylate, and a core-shell graft copolymer was obtained in the same manner as in Comparative Preparation Example 7, except that 15 parts by weight of methyl methacrylate was added instead of 13 parts by weight and 5 parts by weight of glycidyl methacrylate was added instead of 2 parts by weight in Comparative Preparation Example 7.
[0130] Examples and Comparative Examples: Preparation of Resin Compositions
[0131] Example 1
[0132] Polybutylene adipate terephthalate (manufacturer: Xinjiang Blue Mountain Tunhe Chemical Co., Ltd., product name: TH801T) and polylactic acid (manufacturer: Natureworks, product name: Ingeo Biopolymer 2003D) were dried at 60° C. for 24 hours in an oven.
[0133] Then, 80 parts by weight of polybutylene adipate terephthalate, 20 parts by weight of polylactic acid, and 0.1 parts by weight of the acrylic copolymer obtained according to Preparation Example 1 were mixed and blended at 60 rpm for 8 minutes at 180° C. using a Haake Rheomix Os laboratory mixer manufactured by Thermo Electron Karlsruhe GmbH. Then, a resin composition was obtained by grinding the obtained mixture.
[0134] Example 2
[0135] A resin composition was obtained in the same manner as in Example 1 except that 0.3 parts by weight of the acrylic copolymer obtained according to Preparation Example 1 was charged, which was different from Example 1 in which 0.1 parts by weight of the acrylic copolymer was charged.
[0136] Example 3
[0137] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer obtained according to Preparation Example 1 was charged, which was different from Example 1 in which 0.1 parts by weight of the acrylic copolymer was charged.
[0138] Example 4
[0139] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer obtained according to Preparation Example 2 was charged, which was different from Example 1 in which 0.1 parts by weight of the acrylic copolymer was charged.
[0140] Example 5
[0141] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer obtained according to Preparation Example 3 was charged, which was different from Example 1 in which 0.1 parts by weight of the acrylic copolymer was charged.
[0142] Example 6
[0143] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer obtained according to Preparation Example 4 was charged, which was different from Example 1 in which 0.1 parts by weight of the acrylic copolymer was charged.
[0144] Example 7
[0145] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer obtained according to Preparation Example 5 was charged, which was different from Example 1 in which 0.1 parts by weight of the acrylic copolymer was charged.
[0146] Example 8
[0147] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer obtained according to Preparation Example 6 was charged, which was different from Example 1 in which 0.1 parts by weight of the acrylic copolymer was charged.
[0148] Comparative Example 1
[0149] A resin composition was obtained in the same manner as in Example 1, except that the acrylic copolymer obtained according to Preparation Example 1 was not charged, which was different from Example 1.
[0150] Comparative Example 2
[0151] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer according to Comparative Preparation Example 1 was charged, which was different from Example 1 in that 0.1 parts by weight of the acrylic copolymer obtained in Preparation Example 1 was charged.
[0152] Comparative Example 3
[0153] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer obtained according to Comparative Preparation Example 2 was added, which was different from Example 1 in which 0.1 parts by weight of the acrylic copolymer obtained in Preparation Example 1 was added.
[0154] Comparative Example 4
[0155] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer obtained according to Comparative Preparation Example 3 was added, which was different from Example 1 in which 0.1 parts by weight of the acrylic copolymer obtained in Preparation Example 1 was added.
[0156] Comparative Example 5
[0157] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer obtained according to Comparative Preparation Example 4 was added, which was different from Example 1 in which 0.1 parts by weight of the acrylic copolymer obtained in Preparation Example 1 was added.
[0158] Comparative Example 6
[0159] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer obtained according to Comparative Preparation Example 5 was added, which was different from Example 1 in which 0.1 parts by weight of the acrylic copolymer obtained in Preparation Example 1 was added.
[0160] Comparative Example 7
[0161] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer obtained according to Comparative Preparation Example 6 was added, which was different from Example 1 in which 0.1 parts by weight of the acrylic copolymer obtained in Preparation Example 1 was added.
[0162] Comparative Example 8
[0163] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer obtained according to Comparative Preparation Example 7 was added, which was different from Example 1 in which 0.1 parts by weight of the acrylic copolymer obtained in Preparation Example 1 was added.
[0164] Comparative Example 9
[0165] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer obtained according to Comparative Preparation Example 8 was added, which was different from Example 1 in which 0.1 parts by weight of the acrylic copolymer obtained in Preparation Example 1 was added.
[0166] Comparative Example 10
[0167] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer obtained according to Comparative Preparation Example 9 was added, which was different from Example 1 in which 0.1 parts by weight of the acrylic copolymer obtained in Preparation Example 1 was added.
[0168] Comparative Example 11
[0169] A resin composition was obtained in the same manner as in Example 1 except that 1 part by weight of the acrylic copolymer obtained according to Comparative Preparation Example 10 was added, which was different from Example 1 in that 0.1 parts by weight of the acrylic copolymer obtained in Preparation Example 1 was added.
[0170] Test example
[0171] Test Example 1
[0172] The glass transition temperature, molecular weight and epoxy equivalent of each acrylic copolymer prepared according to Preparation Examples 1 to 6 and Comparative Preparation Examples 2 to 10 were measured by the following method, and the measurement results are listed in the following Table 1 together with the structure and monomer composition of the copolymer.
[0173] Furthermore, the glass transition temperature, molecular weight, and epoxy equivalent of the copolymer according to Comparative Preparation Example 1 were measured, and the measurement results are listed in Table 1 below.
[0174] Glass transition temperature (°C): The glass transition temperature was measured using a differential scanning calorimeter (manufacturer: TA Instruments, model name: DSC 250) in the following manner: 8 mg (error range 1 mg) of a sample of each acrylic copolymer prepared according to the Preparation Example and the Comparative Preparation Example was added; the mixture was initially heated to 300°C at a heating rate of 10°C / min under a nitrogen flow; the mixture was cooled to 0°C at a cooling rate of 10°C / min; and the mixture was secondarily heated to 300°C at a heating rate of 10°C / min.
[0175] Weight average molecular weight and number average molecular weight: The weight average molecular weight and number average molecular weight of the obtained acrylic copolymer sample were measured under the following conditions using gel permeation chromatography (GPC, PL GPC220, manufactured by Agilent Technologies Co., Ltd.) In this case, a part of a solution dissolved in a solvent of tetrahydrofuran (stabilized with BHT) at a concentration of 2 mg / ml was taken and used as a sample.
[0176] - Column: PL MiniMixed BX 2
[0177] -Solvent: Tetrahydrofuran (stabilized with BHT)
[0178] -Flow rate: 0.3ml / min
[0179] -Sample concentration: 2.0mg / ml
[0180] - Column temperature: 40℃
[0181] -Detector: Waters 2414 Refractive Index Detector
[0182] -Data processing: Empower
[0183] -Calibration curve: using polystyrene standards (nine molecular weights: 2,000 / 10,000 / 30,000 / 70,000 / 200,000 / 700,000 / 2,000,000 / 4,000,000 / 10,000,000)
[0184] Epoxy equivalent (g / eq): According to nuclear magnetic resonance spectroscopy, the amount ratio (molar ratio) of glycidyl methacrylate was measured using a 700 MHz NMR spectrometer manufactured by Bruker Co., Ltd., and the equivalent number of epoxy groups (eq / mol) was obtained from the measured value, and the epoxy equivalent (g / eq) was calculated by using the number average molecular weight (Mn) measured above.
[0185] [Table 1]
[0186]
[0187]
[0188]
[0189] Test Example 2
[0190] The resin compositions prepared according to Example 1 and Comparative Example 1 were respectively placed in a mold having a size of 130 mm x 130 mm x 2 mm, preheated at 180°C for about 5 minutes, and then press-treated at a compressive load of 20 MPa for 3 minutes, and then quenched at room temperature to prepare a specimen. Subsequently, a cross section of the specimen was microtomed using a transmission electron microscope and magnified at a magnification of 25,000, and the specimens were respectively Figure 1 (Example 3) and Figure 2 (Comparative Example 1) is shown.
[0191] like Figure 1 As shown in , in Example 3, the domains of polylactic acid (bright area) exist alone in polybutylene adipate terephthalate (dark area). It can be confirmed that even the largest domain has a domain size of less than about 0.5 μm relative to the major axis of the domain, so the domains of polylactic acid are formed in a very small size.
[0192] On the other hand, Figure 2 As shown in , in Comparative Example 1 in which no compatibilizer is added, the domain of polylactic acid (bright area) exists alone in polybutylene adipate terephthalate (dark area). It can be confirmed that the domain size is in the range of about 0.5 μm to about 1.5 μm relative to the long axis of the domain, so the domain of polylactic acid is formed in a large size.
[0193] exist Figure 1 and Figure 2 The average diameter of the domain relative to the long axis of the domain was analyzed using the Analyze tool of the ImageJ software. As a result, it was confirmed that the average diameter of the polylactic acid domain relative to the long axis of the domain in Example 3 was about 0.3 μm, and the average diameter of the polylactic acid domain relative to the long axis of the domain in Comparative Example 1 was about 1.2 μm.
[0194] From these results, it was confirmed that the resin composition prepared according to the example of the present invention had improved compatibility between polylactic acid and polybutylene adipate terephthalate due to the acrylic copolymer, so that the polylactic acid was finely and uniformly dispersed.
[0195] Test Example 3
[0196] The molecular weight and molecular weight distribution, tensile strength, elongation and melt flow index of the resin compositions prepared according to Examples 1 to 8 and Comparative Examples 1 to 11 were measured in the following manner, and the results are listed in Table 2 below.
[0197] Weight average molecular weight, number average molecular weight, molecular weight distribution and molecular weight increase rate: The weight average molecular weight and number average molecular weight of the obtained resin composition sample were measured under the following conditions using gel permeation chromatography (GPC, PL GPC220, manufactured by Agilent Technologies Co., Ltd.) In this case, a part of a solution obtained by dissolving in a solvent chloroform at a concentration of 1 mg / ml was taken and used as a sample.
[0198] - Column: PL MiniMixed BX 2
[0199] -Solvent: Chloroform
[0200] -Flow rate: 1.0ml / min
[0201] -Sample concentration: 1.0mg / ml
[0202] - Column temperature: 40℃
[0203] -Detector: Waters 2414 Refractive Index Detector
[0204] -Data processing: Empower
[0205] -Calibration curve: using polystyrene standards (nine molecular weights: 2,000 / 10,000 / 30,000 / 70,000 / 200,000 / 700,000 / 2,000,000 / 4,000,000 / 10,000,000)
[0206] In addition, the increase rate of the weight average molecular weight measured for the resin compositions according to Examples 1 to 8 and Comparative Examples 2 to 11 relative to the weight average molecular weight measured for the resin composition according to Comparative Example 1 without adding an acrylic copolymer was calculated according to the following Equation 1, and the calculation results are listed.
[0207] [Equation 1]
[0208] Molecular weight increase rate = (weight average molecular weight measured according to the resin compositions of Examples 1 to 8 and Comparative Examples 2 to 11 / weight average molecular weight measured according to the resin composition of Comparative Example 1) x 100
[0209] Tensile strength and elongation: The obtained resin compositions were respectively placed in molds having a size of 130 mm × 130 mm × 2 mm, preheated at 180° C. for about 5 minutes, and then press-treated at a compressive load of 20 MPa for 3 minutes, and then quenched at room temperature to prepare specimens. The prepared specimens were prepared as test specimens according to ASTM D638, Type 4 standard, and the elongation and tensile strength were measured under the condition of 50 mm / min using a universal physical property tester (Instron 3365) manufactured by Instron Co., Ltd. according to ASTM D638 standard.
[0210] Melt flow index (g / 10 min): The melt flow index of a resin composition sample was measured using MI-4 manufactured by Gottfert Co., Ltd in accordance with ASTM D1238 (190° C., 5 kg).
[0211] [Table 2]
[0212]
[0213] As shown in Table 2 above, it can be confirmed that, compared with the resin composition prepared according to Comparative Example 1 without containing a compatibilizer, the resin composition according to Comparative Example 2 containing the copolymer disclosed in Patent Document 1 as a compatibilizer has a significantly increased weight average molecular weight, and thus exhibits increased tensile strength, but due to the rapid increase in viscosity, the melt flow index is too low and does not appear, and the elongation is reduced instead.
[0214] Meanwhile, it can be confirmed that the resin compositions prepared according to Examples 1 to 8 including the acrylic copolymer defined according to the present invention have increased tensile strength while maintaining an elongation equal to or greater than that of the resin composition prepared according to Comparative Example 1, compared to the resin composition not including the compatibilizer prepared according to Comparative Example 1. Specifically, it can be confirmed that the resin compositions prepared according to Examples 1 to 8 have a higher melt flow index than the resin composition including the same amount of the compatibilizer according to Comparative Example 2, and thus exhibit excellent processability.
[0215] At the same time, it can be confirmed that in the resin compositions prepared according to Comparative Examples 3 to 5, the acrylic copolymers prepared according to Comparative Preparation Examples 2 to 4, which contain a small amount of (meth)acrylate monomer units containing epoxy groups and contain excess methyl (meth)acrylate monomer units and (meth)acrylate alkyl ester monomer units having 2 to 10 carbon atoms, are used as compatibilizers. Even if the addition of the compatibilizer is increased, the change in processability caused by the melt flow index and the tensile properties is very small.
[0216] In addition, it can be confirmed that in the resin compositions prepared according to Comparative Examples 6 and 7, the acrylic copolymers containing a large amount of (meth)acrylate monomer units containing epoxy groups and a small amount of methyl (meth)acrylate monomer units prepared according to Comparative Preparation Examples 5 and 6 are used as compatibilizers. Since the amount of (meth)acrylate monomer units containing epoxy groups increases, the epoxy equivalent in the acrylic copolymer increases sharply, so the interface adhesion between PLA and PBAT becomes too high, and thus the elongation is significantly reduced.
[0217] In addition, it can be confirmed that in the resin compositions prepared according to Comparative Examples 8 to 11 using the core-shell acrylic copolymers prepared according to Comparative Preparation Examples 7 to 10 as a compatibilizer, the compatibility between PLA and PBAT is considerably hindered, and thus the tensile properties become worse.
[0218] With regard to these results, it can be seen that the resin composition of the present invention uses a chemical compatibilizer to improve the compatibility between heterogeneous biodegradable resins, thereby improving the compatibility and having excellent mechanical properties.
Claims
1. A resin composition comprising: a first biodegradable resin and a second biodegradable resin; and at least one of an acrylic copolymer and a compatible portion formed from the acrylic copolymer, in, The acrylic copolymer comprises a methyl (meth)acrylate monomer unit, an epoxy-containing (meth)acrylate monomer unit, and an alkyl (meth)acrylate monomer unit having 2 to 10 carbon atoms, and the epoxy-containing (meth)acrylate monomer unit contains 15 to 60 wt %.
2. The resin composition according to claim 1, wherein The first biodegradable resin includes an aliphatic polyester unit and an aromatic polyester unit.
3. The resin composition according to claim 1, wherein The first biodegradable resin includes polybutylene adipate terephthalate.
4. The resin composition according to claim 1, wherein The second biodegradable resin includes polylactic acid.
5. The resin composition according to claim 1, wherein The second biodegradable resin may be included in an amount of 1 to 50 parts by weight relative to 100 parts by weight of the first biodegradable resin.
6. The resin composition according to claim 1, wherein The acrylic copolymer and at least one of the compatible part formed of the acrylic copolymer may be contained in an amount of 0.01 to 10 parts by weight relative to 100 parts by weight of the first biodegradable resin.
7. The resin composition according to claim 1, wherein The acrylic copolymer comprises 25 to 65 wt % of methyl (meth)acrylate monomer units, 15 to 60 wt % of (meth)acrylate monomer units containing epoxy groups, and 5 to 30 wt % of alkyl (meth)acrylate monomer units having 2 to 10 carbon atoms.
8. The resin composition according to claim 1, wherein The acrylic copolymer has an epoxy equivalent weight (EEW) of 200 g / eq to 800 g / eq.
9. The resin composition according to claim 1, wherein The acrylic copolymer has a weight average molecular weight of 10,000 to 100,000.
10. The resin composition according to claim 1, wherein The acrylic copolymer has a glass transition temperature of 45°C to 85°C.
11. The resin composition according to claim 1, wherein The weight average molecular weight of the entire resin composition is 100,000 to 200,000.
12. The resin composition according to claim 1, wherein The resin composition has a melt flow index of 3 to 13.5 g / 10 min, measured at 190° C. with a load of 5 kg according to ASTM D1238.
13. The resin composition according to claim 1, wherein The tensile strength of the resin composition measured according to ASTM D638 is 245 kgf / cm 2 Up to 500kgf / cm 2 .
14. The resin composition according to claim 1, wherein The resin composition has an elongation of 400% or more measured according to ASTM D638.
15. The resin composition according to claim 1, wherein When a sample of the resin composition was magnified at a magnification of 25,000 using a transmission electron microscope, the average diameter of the domains observed was 1 μm or less relative to the major axis of the domains.
16. A molded product molded from the resin composition according to any one of claims 1 to 15.
